The Students Difficulties in Comprehending Reading Text at the Eleventh Grade of SMA Negeri 6 Sigi : Kesulitan Siswa dalam Memahami Bacaan Teks Kelas Sebelas di SMA Negeri 6 Sigi - Irmawati; Nadrun; Sari Wulandari (Jurnal Kolaboratif Sains, 2021)
This research was conducted to find out the students’ difficulties in comprehending English reading narrative text. The subject of the research was the eleventh grade IPA 1 students of SMA Negeri 6 Sigi. The research used descriptive qualitative method. The instruments were test and interview. The test was used to gain data of the students’ difficulties in comprehending reading text. Furthermore, the interview was used to support the data about the students’ difficulties in comprehending reading text. The finding showed that the students’ difficulties are lack of vocabulary, low ability in comprehending narrative text, not have enough understanding about the general structure and types of narrative text, have no interest in English reading text, bored in reading English texts, and difficulties used past tense in narrative text. In other words, the students at the eleventh grade of SMA Negeri 6 Sigi still got difficulties in comprehending reading narrative text.